STRATEGY ALIGNMENT WITH VALUE CHAIN FOR SUSTAINABLE GROWTH IN TECHNOLOGY RELATED INDUSTRIES - KIPTOO, BETT SAMWEL (My University, 2013)
The threat come from cloths from Asian countries for the high and middle income bracket and “mitumba” for low income which we can generalized that the main threat is from substitute products that have flooded the market. Hence this a market which filled with cheap product and it mean that specific strategies must be established and implement
Keywords: CHAIN FOR SUSTAINABLE GROWTH